Optimization of ultrasound-mediated DNA transfer for bacteria and preservation of frozen competent cells - Meng Zhang; Rongkang Tang; Fang-Xia Li; Wen-Yu Jin; Jia-Xin Guo; Lin-Zuo Teng; Guangxun Meng; Philippe J. Sansonetti; Yi-Zhou Gao (Microbiology Spectrum)
ABSTRACT The transformation of DNA into cells is the basis of molecular biology. Commonly employed techniques include heat shock transformation, electro-transformation, conjugation, transduction, and protoplast fusion. Recently, ultrasonic transformation technology has been developed to transfer DNA into competent cells. The transformation conditions, such as temperature and ultrasonic power, were preliminarily studied. However, this technique has not been widely applied because competent cells must be prepared de novo. In this study, various factors, such as ultrasonic frequency and power, were optimized for the ultrasonic transformation of Escherichia coli. The study found that the optimal conditions for ultrasonic transformation with a defined ultrasonic transformation vial were a frequency of 28 kHz and a power of 80 W. Meanwhile, this research demonstrated that combining the 42°C heat shock conditions with ultrasonic transformation is the most efficient method compared to using only heat shock. Furthermore, the cryoprotective agent ratio for ultrasonic competent cells was investigated and optimized. These findings provide new insights into enhancing transformation efficiency and lay a foundation for the broader application of ultrasonic transformation.IMPORTANCEPlasmid transformation is widely applicable in gene expression and modification. As an efficient, non-invasive, and gentle method of transformation, ultrasonic transformation provides a novel approach for strain modification. This research presents new strategies for enhancing transformation efficiency and lays the groundwork for expanding the utilization of ultrasonic transformation.